Present-day capitalist urbanization and unequal disaster risk production: the case of Tigre, Buenos Aires - Ríos, Diego Martín (2015)
This paper describes recent urban transformations in flood-prone areas on the outskirts of Buenos Aires that, prompted by a convergence of public–private interests, ignore the adverse consequences they generate and produce deeply unequal exposure to disaster risks. To illustrate these processes and their spatial results, the paper looks at the case of the municipality of Tigre, located to the north of the metropolis. I analyse the most substantive changes in public urban management and implementation of water management projects that have tended over recent decades to facilitate the operation of real estate/financial capital, through the development of degraded flood-prone risk areas that has made these the subject of dispute between antagonistic social groups.